When Financing and Tax Strategies Shape Corporate Responsibility: Examining the Effects of Capital Structure and Tax Avoidance on CSR Implementation - Ni Putu Budiadnyani; Ketut Tanti Kustina (Universitas Muhammadiyah Makassar, 2025)
This study examines the interconnected effects of capital structure and tax avoidance on corporate social responsibility (CSR) implementation among food and beverage companies listed on the Indonesia Stock Exchange from 2021 to 2023. While corporate financing decisions and tax strategies are often viewed as mechanisms that shape resource allocation and managerial priorities, their influence on CSR engagement remains empirically contested. Using purposive sampling, the research analyzes firms that consistently published financial reports and used the Rupiah as their reporting currency during the observation period. Capital structure is measured through the debt-to-equity ratio, tax avoidance is assessed using the Cash Effective Tax Rate, and CSR implementation is evaluated using aggregated environmental, social, and governance (ESG) scores. Multiple regression analysis reveals that neither tax avoidance nor capital structure exerts a significant effect on CSR implementation. These findings diverge from prevailing theoretical expectations grounded in agency theory, trade-off theory, and compliance theory, which suggest that aggressive tax strategies or high leverage could undermine a firm’s commitment to socially responsible practices. The results indicate the possibility of moderating or mediating influences such as political connections, managerial ethics, governance quality, or investment opportunities that may weaken the direct relationship between financial strategies and CSR outcomes. The study contributes to the growing discourse on corporate responsibility by highlighting the need for more nuanced models that integrate ethical, organizational, and institutional factors when evaluating how firms balance financial decisions with their social obligations.